The wearable activity technology and action-planning trial in cancer survivors: Physical activity maintenance post-intervention. Issue 9 (September 2021) - Hardcastle, Sarah J.; Maxwell-Smith, Chloé; Hince, Dana; Bulsara, Max K.; Boyle, Terry; Tan, Patrick; Levitt, Michael; Salama, Paul; Mohan, Ganendra Raj Kader Ali; Salfinger, Stuart; Makin, Gregory; Tan, Jason; et al.
Abstract: Objectives: The study objective was to assess whether moderate-to-vigorous intensity physical activity (MVPA) change in cancer survivors ( n  = 68, mean age = 64 years) was maintained 12-weeks following the Wearable Activity Technology and Action Planning (WATAAP) intervention. Secondary aims were to assess the effects of the intervention on blood pressure (BP) and body mass index (BMI), and to explore group differences between baseline and 24-weeks. Design: Randomized controlled trial. Methods: MVPA and sedentary behaviour were assessed using an accelerometer at baseline, the end of the intervention (12-weeks), and at 24-weeks. Generalised linear mixed models with random effects were used to examine between-group and within-group changes in MVPA, sedentary behaviour, BP and BMI. Results: MVPA was significantly higher in the intervention group compared with the control group at 24-weeks following adjustment for known confounders (141.4 min/wk. (95% CI = 9.1 to 273.8), p  = 0.036). At 24-weeks participants in the intervention group had maintained their increased levels of MVPA (change from 12-weeks = 8.8 min/wk.; 95% CI = −43 to 61; p  = 0.74). The reduction in MVPA in the control group over the first 12-weeks was also maintained at 24-weeks (5.4 min/wk.; 95% CI = −3.6 to 4.6; p  = 0.80). Secondary outcomes did not differ between groups at 24-weeks. Conclusions: Our results suggest distance-based interventions using wearable technology produce increases in MVPA that endure at least 12-weeks after the intervention is completed.